Introduction To Stress Management In Students In The Covid-19 Pandemic - Baharuddin; Meutia Yusuf; Ibrahim (Institute of Computer Science (IOCS), 2022)
We can see the impact of COVID-19 from various aspects, one of which is education. Education is an aspect that has been greatly affected by the pandemic. The imposition of social restrictions due to the Covid-19 pandemic implemented in the field of education in the form of distance learning is a serious problem for students. Uncertainty in aspects of life has caused stress in some students. Stress conditions have affected individual mental health so that it affects daily activities. Stress can cause disturbances in immunity as well as cause anxiety disorders and depression. This study aims to analyze stress management in students during the Covid 19 pandemic. The method used is the provision of health education with lectures, questions and answers, discussions, demonstrations, and re-demonstrations. Before the implementation of the activity, a pre-test was carried out and after that a post-test was carried out using a questionnaire. The results showed an increase in participants' knowledge and attitudes about how to do stress management. This shows the provision of health education using a variety of effective methods to increase knowledge. Alternatives to managing student stress include maximizing counseling services, implementing counseling, time management, setting guidance schedules with supervisors, setting graduation targets and seeking social support. This shows the provision of health education using a variety of effective methods to increase knowledge. Alternatives to managing student stress include maximizing counseling services, implementing counseling, time management, setting guidance schedules with supervisors, setting graduation targets and seeking social support.